2017
DOI: 10.1016/s1474-4422(17)30124-2
|View full text |Cite|
|
Sign up to set email alerts
|

Neurofilament light protein in blood as a potential biomarker of neurodegeneration in Huntington's disease: a retrospective cohort analysis

Abstract: SummaryBackgroundBlood biomarkers of neuronal damage could facilitate clinical management of and therapeutic development for Huntington's disease. We investigated whether neurofilament light protein NfL (also known as NF-L) in blood is a potential prognostic marker of neurodegeneration in patients with Huntington's disease.MethodsWe did a retrospective analysis of healthy controls and carriers of CAG expansion mutations in HTT participating in the 3-year international TRACK-HD study. We studied associations be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

40
315
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 307 publications
(360 citation statements)
references
References 27 publications
40
315
0
5
Order By: Relevance
“…Recently, there has been great interest in the potential utility of NF-L in blood as a biomarker for several neurodegenerative diseases including AD, MS, progressive supranuclear palsy (PSP), ALS, and Huntington’s disease [43, 71, 228, 240, 302, 385, 408], as well as a marker of traumatic brain injury [224, 324]. In AD, plasma or serum levels of NF-L have been shown to be elevated compared with controls in presymptomatic individuals known to be carriers of AD-causing gene mutations [385] and subjects with MCI or AD [240, 408].…”
Section: Other Neuronal Proteinsmentioning
confidence: 99%
“…Recently, there has been great interest in the potential utility of NF-L in blood as a biomarker for several neurodegenerative diseases including AD, MS, progressive supranuclear palsy (PSP), ALS, and Huntington’s disease [43, 71, 228, 240, 302, 385, 408], as well as a marker of traumatic brain injury [224, 324]. In AD, plasma or serum levels of NF-L have been shown to be elevated compared with controls in presymptomatic individuals known to be carriers of AD-causing gene mutations [385] and subjects with MCI or AD [240, 408].…”
Section: Other Neuronal Proteinsmentioning
confidence: 99%
“…4). Also, the zQ175 mice showed a decrease in immunodensity of neurofilament, a biomarker of HD [33,34], which was partially corrected after P110 treatment (Fig. 4).…”
Section: Resultsmentioning
confidence: 99%
“…In summary, the study reported by Byrne and colleagues 4 represents a major advance in the field of Huntington's disease and neurodegeneration in general, and it seems likely to presage further advances in disease biology and, most importantly, in experimental therapeutics.…”
Section: *Massimo Filippi Maria a Roccamentioning
confidence: 90%
“…2 It shows that plasma concentrations of neurofilament light (NfL) chain are substantially increased in Huntington's disease and correlate well with age and CAG repeat length. 4 NfL concentrations were as much as 3·6 times greater in patients with manifest Huntington's disease compared with controls, and there was a very clear gradient from controls to early premanifest (far from expected motor onset), late premanifest (close to expected motor onset), and then to manifest Huntington's disease. The NfL increases in manifest Huntington's disease were similar to those in multiple sclerosis relapses, 5 and were at least as great as in other neurodegenerative diseases including progressive supranuclear palsy, 6 multiple system atrophy, 7 and corticobasal syndrome.…”
mentioning
confidence: 91%
See 1 more Smart Citation